Safety leadership practices for organizational safety compliance: developing a research agenda from a review of the literature - Pilbeam, Colin; Doherty, Noeleen; Davidson, Ross; Denyer, David (Elsevier, 2016)
Safety leadership is asserted to positively influence safety compliance amongst employees. We examine this assertion by conducting a systematic literature review of the available academic literature on safety leadership practices and observed safety outcomes. We identified 25 empirical studies, the majority of which measured leadership through generic scales (MLQ and LMX). Closer scrutiny of the outcome measures suggested that these were mainly aligned to the implementation and operations phases of the OHSAS 18001 safety management systems framework. We conclude that safety compliance has been narrowly defined in academic study, but in practice embraces a much wider range of activities. While safety leadership may contribute to successfully achieving these other actions, there is no empirical evidence for this. Moreover, there is considerable critique of transformational and transactional leadership, so that the specification of desired leadership practices is problematic. We propose that a broader conceptualization of safety compliance requires safety leadership to embrace ‘plural’ forms of leadership. We draw attention to the narrow range of contexts in which safety leadership has been empirically studied and suggest other settings for investigation. Alternative methods for investigating safety leadership other than scales of leadership behaviour are suggested to enrich our understanding of safety leadership and so improve safety compliance.
Keywords: Leadership; Compliance; Regulated environments; Self-regulation; Safety participation